Integrating Entrepreneurship Services into Local Workforce Development Systems: Who is Doing It and How. Issue 3 (2nd July 2016) - Harper-Anderson, Elsie L.; Gooden, Susan T.
ABSTRACT: Entrepreneurship has been touted as a potential tool for reducing inequities and poverty in urban areas. This study examines how public workforce funds are being used to support entrepreneurship based on survey responses from administrators in four states. Results suggest that few workforce funds are being used to support entrepreneurship and when they are, it is more likely affluent communities than disadvantaged ones. This could mean that important opportunities for the most disadvantaged residents and communities are being overlooked. Universal access to the entrepreneurship option can play an important role in helping some of the unemployed achieve self-sufficiency.